Services and the Business Models of Product Firms: An Empirical Analysis of the Software Industry - Suarez, Fernando F.; Cusumano, Michael A.; Kahl, Steven J. (Management Science, 2013)
Some product firms increasingly rely on service revenues as part of their business models. One possible explanation is that they turn to services to generate additional profits when their product industries mature and product revenues and profits decline. We explore this assumption by examining the role of services in the financial performance of firms in the prepackaged software products industry (Standard Industrial Classification code 7372) from 1990 to 2006. We find a convex, nonlinear relationship between a product firm's fraction of total sales coming from services and its overall operating margins. As expected, firms with a very high level of product sales are most profitable, and rising services are associated with declining profitability. We find, however, that additional services start to have a positive marginal effect on the firm's overall profits when services reach a majority of a product firm's sales. We show that traditional industry maturity arguments cannot fully explain our data. It is likely that changes in both strategy and the business environment lead product firms to place more emphasis on services. This paper was accepted by Christoph Loch, R&D and product development.